Is the Time Right for a Paradigm Shift? Where we have been and where we Might be Going - Verrecchia, P.J. (International Journal of Criminology and Sociology, 2022)
Over the years there have been a number of paradigms and concomitant shifts in criminal justice. Each paradigm shift follows a general discontentment with the existing paradigm. This is crucial because with change comes a new operating system designed to, at the least, protect society. When the paradigm is not doing its job, crisis can ensue. Current attitudes towards the criminal justice system raise the question, are we in a moment of crisis? This article explores the history of shifts in the criminal justice system, where we are now, and were we might be going.